Pengaruh Kinerja Keuangan, Profil Perusahaan, Kepemilikan Manajerial, Kebijakan Deviden, Dan Dewan Komisaris Terhadap Pengungkapan Corporate Social Responsibility - Meisa Widhaningrum; Rina Trisnawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze whether financial performance, company profile, managerial ownership, dividend policy, and board of commissioners affect Corporate Social Responsibility disclosure in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2022. The population in this study consists of all manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2022, totaling 228 companies. This research utilizes secondary data obtained from the annual reports of companies listed on the IDX from 2019 to 2022. The sampling technique employed is purposive sampling method, resulting in a sample of 23 companies with data analyzed from 92 companies over the years 2019 to 2022. Data collection is conducted through documentation method with multiple linear regression analysis technique. The research findings indicate that only one variable, namely financial performance, significantly influences CSR disclosure, while the other four variables, namely company profile, managerial ownership, dividend policy, and board of commissioners, do not have a significant influence on CSR disclosure.